Governance, overtourism and impacts in Malaga, Spain: Recommendations for sustainability. - Almeida-García, Fernando; Cortés-Macías, Rafael; Mena Navarro, Alfredo; García-Mestanza, Josefa (My University, 2023)
Governance, Overtourism and Impacts in Malaga, Spain: Recommedations for Sustainability This research aims to understand the relationships between governance, overtourism and the impacts of tourism on residents. To this end, this study proposes a novel research model in which governance and overtourism factors are related to social and environmental impacts. In view of the intensification of tourism in the most overcrowded urban destinations in Europe and the Mediterranean, it is necessary to develop sustainable management measures. We conducted a survey of the residents of the municipality of Malaga, Spain. We conducted a factor analysis and regression and proxy maps of the main variables. We created a specific questionnaire to analyse the main factors affecting tourism management and its impacts. The survey is statistically representative (n=450). The results highlight the relationship between municipal governance and overtourism, and how the latter causes the social and environmental impacts of tourism. Impacts related to environmental problems are the most negatively valued by residents and affect their quality of life. A novel investigation is carried out on the relationships between the perception of tourism governance, tourist saturation and the impacts of tourism in a crowded space such as the historic centre of the city of Malaga, Spain.
chrome-extension://efaidnbmnnnibpcajpcglclefindmkaj/https://iatour.org/icot2023/wp-content/uploads/2023/06/Book-of-Abstracts-ICOT2023-ver.1.pdf
Keywords: Turismo - Aspectos sociales; Málaga - Desarrollo comunitario urbano; Saturación turística; Impactos del turismo; Centros históricos; Turistificación; Málaga